Improving development aid design and evaluation: Plan for sailboats, not trains - and Kleinfeld, Rachel (Carnegie Endowment for International Peace, 2015)
How do reforms that require political engagement differ from traditional technical reforms? Why is political engagement different, and what are the implications for design and evaluation? How should development programmes that engage politics be designed? And how can those who fund or implement such programmes evaluate whether their efforts are contributing to reform? This report …
Keywords: IMPORTANT